A retrospective audit comparing state patients with schizophrenia and bipolar mood disorder who have committed violent crime admitted to the male forensic unit at Valkenberg Hospital - Maharaj, Avani (Department of Psychiatry and Mental Health, 2020)
Background There is a consensus that psychosis confers a modest risk toward violent offending. Most research to date has shown that a statistical relationship does exist between schizophrenia and bipolar disorder, and violence and aggressive behavior In forensic mental health, state patients are rehabilitated in a general program regardless of diagnosis. It is not known whether different rehabilitation management strategies should be implemented on those with bipolar disorder as compared to those with schizophrenia. This study is an attempt to ascertain if there are differences between those diagnosed with schizophrenia and bipolar disorders, and if so, whether these have implications for their rehabilitation programs. Objectives The study aims to compare the demographic profiles and comorbidities (in terms of substance use and personality disorders) of state patients with bipolar disorder and schizophrenia who have offended violently. Methods This was a quantitative, cross sectional study. State patients who were diagnosed with schizophrenia and bipolar disorder and committed a violent crime were included in the study from the 1st January 2000 to 31st December 2014. The study population comprised a total of 93 male state patients. Of these 46 patients had a diagnosis of bipolar disorder and 47 patients had a diagnosis of schizophrenia. Results The results show that in general the differences between the schizophrenia group and the bipolar disorder group are marginal. A higher percentage of patients with schizophrenia committed murder at 17.02% and attempted murder at 12.77%. The bipolar disorder group had a significantly higher number of patients diagnosed with co morbid personality disorder at 59.57% (p value of 0.01.) Substance abuse was common in both groups. The mean age at admission was 31,23 years in schizophrenia and 36,85 years in bipolar disorder. This demonstrates an earlier onset of criminality in the group with schizophrenia. Patients with bipolar disorder were more likely to be married (13.04%), divorced (10.8%) or separated (2.17%). Conclusion There were no major differences elicited between the 2 groups of patients. Certain aspects such as therapeutic programs for personality disordered patients and social interventions in patients with poor social support would contribute to improving the quality of the rehabilitation programs currently used. The commonalities found in the 2 groups suggest that a common approach to rehabilitation would be adequate in this setting.